Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1021/acsami.3c00163
|View full text |Cite
|
Sign up to set email alerts
|

Structural Construction of Au–Pd Nanocomposite for Alkali-Free Oxidation of Benzyl Alcohol

Abstract: A bimetallic Au−Pd system is an alternative candidate to catalyze primary alcohol oxidation and is of crucial importance for the sustainable chemical industry. However, understanding the bimetallic system in terms of the nanostructure is still challenging. Herein, we adopt the in situ colloid immobilization to obtain a series of bimetallic Au x Pd y /CNT samples supported by carbon nanotubes (CNTs). Elaborate characterizations confirmed the bimetallic structure of AuPd alloy particles with randomly dispersed P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…22,23 For instance, Au and Pd-codoped carbon nanotubes exhibit high catalytic performance in the oxidation of benzyl alcohol to benzaldehyde with the selectivity of 91.8% in that the interactions between Au and Pd cause benzyl alcohol to be more readily adsorbed and then activated. 24 Considering that the Mo-peroxo species (Mo−O 2 ) produced between the Mo complexes and peroxides facilitates selective oxidation of alcohol to aldehyde, 25 whereas Mo(VI) alone cannot activate O 2 to the Mo−O 2 peroxo, 26 we then hypothesize that the coupled Bi−Mo sites will also facilitate the formation of the surface Mo−O 2 peroxo, which then selectively oxidizes benzyl alcohol to benzaldehyde. Alkaline conditions are favorable in initiating H-abstraction from benzyl alcohol to benzaldehyde and facilitate stabilization of the surface peroxo.…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 For instance, Au and Pd-codoped carbon nanotubes exhibit high catalytic performance in the oxidation of benzyl alcohol to benzaldehyde with the selectivity of 91.8% in that the interactions between Au and Pd cause benzyl alcohol to be more readily adsorbed and then activated. 24 Considering that the Mo-peroxo species (Mo−O 2 ) produced between the Mo complexes and peroxides facilitates selective oxidation of alcohol to aldehyde, 25 whereas Mo(VI) alone cannot activate O 2 to the Mo−O 2 peroxo, 26 we then hypothesize that the coupled Bi−Mo sites will also facilitate the formation of the surface Mo−O 2 peroxo, which then selectively oxidizes benzyl alcohol to benzaldehyde. Alkaline conditions are favorable in initiating H-abstraction from benzyl alcohol to benzaldehyde and facilitate stabilization of the surface peroxo.…”
Section: T H Imentioning
confidence: 99%
“…How to ensure the high photooxidation selectivity of benzyl alcohol toward benzaldehyde without introducing additives is therefore an interesting topic. Till now, bimetallic catalysts have been recognized to be effective in improving catalytic reactivity and selectivity owing to the synergistic effects of the bimetallic sites. , For instance, Au and Pd-codoped carbon nanotubes exhibit high catalytic performance in the oxidation of benzyl alcohol to benzaldehyde with the selectivity of 91.8% in that the interactions between Au and Pd cause benzyl alcohol to be more readily adsorbed and then activated . Considering that the Mo-peroxo species (Mo–O 2 ) produced between the Mo complexes and peroxides facilitates selective oxidation of alcohol to aldehyde, whereas Mo­(VI) alone cannot activate O 2 to the Mo–O 2 peroxo, we then hypothesize that the coupled Bi–Mo sites will also facilitate the formation of the surface Mo–O 2 peroxo, which then selectively oxidizes benzyl alcohol to benzaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Sun et al, [17] reported a PdÀ Au/MCN catalyst for oxidation of alcohol, while Tobita et al, [12] presented the NCIÀ Cu nanocatalyst, which shows good catalytic activity in oxidation alcohols at a temperature of 60 °C. Additionally, Luo et al, [18] reported the AuÀ Pd/CNT nanocomposite catalyst activity in the oxidation of alcohol at a temperature above 80 °C and gave up to 91.8 % selectivity. Despite these advancements, many of these catalysts still require elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…While extensive research has been dedicated to identifying suitable catalyst materials over an extended period, comprehending catalytic mechanisms through the lens of surface science offers a systematic approach. Traditionally, noble metals such as Pt have been recognized as prominent catalysts, capitalizing on their ability to furnish a substantial active area to reactants and mitigate catalyst deactivation. Nevertheless, the formation of bimetallic catalysts has revealed their potential to significantly outperform existing noble metal catalysts due to the distinctive occurrence of atomic interfaces. , This encompasses alloy types that influence electronic characteristics by altering atomic arrangements, as well as phase-separation types where distinct phases can synergistically or organically undertake roles through independent spatial segregation. Despite numerous experimental findings showcasing heightened catalytic activity in heterogeneous compounds, there remains a scarcity of quantitative or experimental discussions addressing the optimization and regulation of the underlying electronic properties driving this phenomenon.…”
Section: Introductionmentioning
confidence: 99%